Legal Awareness and Community Empowerment: Assessing the Effectiveness of Community-Based Legal Assistance Services - Suryani; Naiema Taliep; Indri Hapsari (Zabags International Journal of Engagement, 2026)
This article examines the effectiveness of community-based legal assistance services in enhancing legal awareness and empowering communities as part of broader efforts to expand access to justice. The study aims to analyze the extent to which such services strengthen individuals’ understanding of legal rights and obligations while simultaneously building their capacity to advocate for social and economic rights. Employing a mixed methods approach with an explanatory sequential design, quantitative analysis was first conducted to measure relationships among variables, followed by qualitative inquiry to explore the dynamics of program implementation. The findings reveal that community-based legal assistance has a significant positive impact on legal awareness, which in turn contributes to greater community empowerment in areas such as decision-making, social participation, and confidence in pursuing rights. Qualitative insights highlight that active community participation in legal education initiatives fosters solidarity and strengthens trust in legal institutions. The study contributes conceptually and methodologically by integrating the Theory of Legal Consciousness, Empowerment Theory, and the Access to Justice Framework within the context of community-based legal services. It also offers practical implications for policymakers and practitioners, recommending more inclusive and participatory legal aid strategies to ensure equitable access to justice for vulnerable groups.